2020
DOI: 10.7717/peerj.10223
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and gene expression analysis ofRhynchophorus ferrugineus(Coleoptera: Curculionidae) during developmental stages

Abstract: Background Red palm weevil, Rhynchophorus ferrugineus Olivier, is one of the most destructive pests harming palm trees. However, genomic resources for R. ferrugineus are still lacking, limiting the ability to discover molecular and genetic means of pest control. Methods In this study, PacBio Iso-Seq and Illumina RNA-seq were used to generate transcriptome from three developmental stages of R. ferrugineus (pupa, 7th-instar larva, adult) to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 97 publications
(107 reference statements)
0
8
0
Order By: Relevance
“…In 2020, two additional transcriptomic studies were conducted with the aim of identifying RPW genes [ 64 , 65 ]. Both studies used the same PacBio long-read isoform sequencing (iso-seq) and Illumina RNA-seq data to generate a full-length transcriptome assembly of the RPW.…”
Section: Omics Technologies and Their Impact On Pest Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, two additional transcriptomic studies were conducted with the aim of identifying RPW genes [ 64 , 65 ]. Both studies used the same PacBio long-read isoform sequencing (iso-seq) and Illumina RNA-seq data to generate a full-length transcriptome assembly of the RPW.…”
Section: Omics Technologies and Their Impact On Pest Sciencementioning
confidence: 99%
“…When mapping Illumina reads to the assembled transcripts, approximately 87%, 89%, 88%, and 88% of the short reads were mapped for male adults, female adults, pupae, and larvae, respectively. Expression analysis found that about 13.45% (8583) of genes are differentially expressed and engaged in metabolic pathways, organ tissue formation, and material transportation in peroxisomes [ 65 ]. Approximately 86% of the identified transcripts could be annotated using several public databases [ 64 ]; in addition, a total of 9618 long noncoding RNAs, 2084 transcription factors, and 2184 alternative splicing events were identified [ 64 ].…”
Section: Omics Technologies and Their Impact On Pest Sciencementioning
confidence: 99%
“…Genes with a similar color have similar expression patterns, which are often functionally correlated. Meanwhile, differential genes were clustered by relative expression level log 2 (ratios) by H-cluster, k -means, and SOM methods . The results showed that the gene expression patterns at different time points of 0.5 and 2 h were similar, but both of them much differed from the control (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…Adenosine modulated a wide range of processes in many gastrointestinal cells [59], and was essential for ATP biosynthesis and CoA biosynthesis required for fatty acid metabolism [60]. Meanwhile, we found that 8(s)-hydroxy-(5z,9e,11z,14z)-eicosatetraenoic acid and 13(s)hotre, which participated in the "arachidonic acid metabolism" and "alpha-linolenic acid metabolism", were upregulated in Group H. "Arachidonic acid metabolism" and "alphalinolenic acid metabolism" are related to fatty acid metabolism [61]. Furthermore, Uengwetwanit et al [23] reported that shrimp growth and development were largely dependent on lipid metabolism.…”
Section: Key Metabolites Play Important Roles In the Growth Of Gfpsmentioning
confidence: 89%